RESPON FISIOLOGIS IKAN JAMBAL SIAM (Pangasius hypopthalamus) PADA SUHU PEMELIHARAAN YANG BERBEDA - Henni Syawal; Yusni Ikhwan S (Berkala Perikanan Terubuk, 2011)
Fish stress may be governed by change of water temperature that increaseboth chatecolamine and cortisal secretion. In high level both hormone have anegative effects on fish immune system. Increasing of cortical in blood plasmawould lead to inhibition of interleukin I and II formation. Thus, fish immunesystem dropped which cause fish suffer from infection and eventually dead.Physiological stress may stimulate increasing of cortical and glucose level ofblood plasma. As such lysozime activity would increase. Increase of bloodglucose is of a normal indicator of stressed fish. An randomized block designexperiment with one factor, have been carried out to evaluate the effect or watertemperature on blood glucose of fish. Three level of water temperature ( 24, 28.and 280C) were applied. It revealed that blood glucose level ranged from 127.23to 192,96gr/dl with maximum level of glucose appeared in fish reared in 240C (12gr/dl), and the lowest at of 32oC.. Blood hemoglobin in accordance with bloodglucose, in which maximum level found in 240C (12 gr/dl). The highesthematocrite level were appeared in treatment of 240C (39,83%). Red BloodNumber of 4.725 X 103 sel/mm3, were found in the water temperature of 240C.